Analysis of Word Classes in Short Story "Maaf" by Putu Wijaya: Morphological Studies - Rengki Afria; Warni; Aldha Kusuma Wardhani (Proceeding International Conference on Malay Identity, 2021)
Abstrack: The research aims to describe word classes that contained in the ‘Maaf’ by Putu Wijaya’s short story. Word class is a word classifiation in units of language with based on the form categories, function, and meaning in the system grammatical. The function of word class is to develop sentence properly based on patterns sentence raw in order to avoid a mistake in the writing of the setence. The method used in this study is a qualitative descriptive method by analyzing the documents that have been obtained and then explained based on word class, compared and combined to form a systematic and a whole results of the study. It can be concluded that the result of the research from ‘Maaf’ by Putu Wijaya’s short story are (1) Noun 613 words. (2) Verb 436 words. (3) Conjunction or particle obtained 424 words. (4) Adverb 303 words. (5) Pronoun 274 words. (6) Adjektive 223 words. (7) Numerals which is only 46 words. Keywords : Morphology, part of speech, short story